Vaccines, Spas and Yellow Fever: Expert Physicians, Professional Honour and the State in the Mid-Nineteenth Century (Theatrum historiae, 2021)
The nineteenth century was a period when the modern sciences claimed they were the best way of improving the lives of the people and attaining useful knowledge about the world. At the same time, it was an era when the Ancien Régime, a plural world of hierarchically organised communities, was morphing into a capitalist society based on equality before the Law and the free competition of goods and ideas. Our article focuses on several aspects of the physicians’ fight for professional consolidation in a changing world: the patterns of institutionalisation of medicine and healthcare as well as the dynamics of professionalisation of healthcare, including the masculinisation of authority and the public acknowledgement of expert authority in connection with the growing legitimacy – and politicisation – of scientific discourse, but also with practices reaffirming the honour and social status of physicians as a profession. We approach this vast topic from a European perspective, tracing trans-imperial and transnational trends and including the colonial dimensions, as well as the interaction of European powers and subjects with extra-European states and peoples.
Keywords: medicine; expertise; institutionalisation; professionalisation; patients; honour